The Influence of Beta-adrenergic Blockade upon Baseline Blood Coagulation and Fibrinolytic Activity and upon the Responses to Venous Occlusion - Butler, M. J; Smith, Muriel; Irving, M. H; Gordon, Y. B; Ratky, S. M; Rivers, J. W. P; Hawkey, C (Thrombosis and Haemostasis, 1975)
Twenty volunteers were assessed for baseline coagulation (Thrombelastography, Factor VIII and platelet count) and fibrinolytic (Euglobulin Lysis Time and Fibrin(ogen) Degradation Products) activity two hours after ingestion of 60 mgm propranolol or an identical placebo administered on a double blind basis. The responses of these parameters to a fifteen minute period of venous occlusion was also assessed.Beta adrenergic blockade reduced baseline FDP titres but did not affect other parameters, nor the local response to venous occlusion. During occlusion no significant change in coagulation activity could be detected in the non-occluded arm, but a small but statistically significant shortening of ELT was observed. Since this effect was prevented by propranolol it is probably mediated through adrenergic mechanisms.Adrenergic stimuli appear to influence episodes of coagulation and fibrinolysis during everyday activity, but do not contribute to baseline levels of coagulation or fibrinolytic function.